Generalized Synchronization of Lorenz Chaotic System with Star Network - Khan, Mohammad Ali (International Journal of Applied Mathematical Research, 2012)
In this paper, we propose the theory for generalized synchronization (GS) of a chaotic star network. We derive sufficient conditions for generalized synchronization of any chaotic system on a star network. The relationship among the state variables at GS are completely known in our method. The effectiveness and feasibility of the synchronization strategy is confirmed and demonstrated by numerical simulation.